Inflammation and stem markers association to PIM1/PIM2 kinase-induced tumors in breast and uterus - Jiménez-García, Manuel-Pedro (Oncotarget, 2017)
The PIM family of Ser/Thr kinase proteins has been implicated in tumorigenesis at different levels. PIM proteins are overexpressed in several tumor types and have been associated with chemoresistance. However, their role in hormone-dependent female tissues has not been explored, especially in the uterus, breast and ovary. We generated conditional transgenic mice with confined expression of human PIM1 or PIM2 genes in these tissues. We characterized the tumoral response to these genetic alterations corroborating their role as oncogenes since they induce hyperproliferation in all tissues and tumors in mammary gland and uterus. Furthermore, we observed a high degree of inflammatory infiltration in these tissues of transgenic mice accompanied by NFAT and mTOR activation and IL6 expression. Moreover, PIM1/2 were overexpressed in human breast, uterine and ovarian tumors, correlating with inflammatory features and stem cell markers. Our data suggest that PIM1/2 kinase overexpression provoke tissue alterations and a large IL6-dependent inflammatory response that may act synergistically during the process of tumorigenesis. The possible end-point is an increased percentage of cancer stem cells, which may be partly responsible for the therapy resistance found in tumors overexpressing PIM kinases.